Development of Soft Skills-Based Islamic Education Curriculum to Enhance Leadership Competencies of Master of Islamic Education Management Graduates - Nur, Ahya Alfiyan; Ningrum, ⁠Istikomah Kusuma; Santy, Santy; Suratman, Suratman (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
The transformation of Indonesian higher education represents a recontextualization of competencies for graduates of the Master of Islamic Education Management (MMPI) programs of glocalization, prioritizing leadership soft skills. This study aims to develop a prototype MMPI curriculum based on Kutai ethnopedagogy that integrates local wisdom soft skills into the 2023 KKNI Graduate Learning Outcomes through the ADDIE model. The research employs a qualitative instrumental case study approach at MMPI UIN Samarinda, applying triangulation of phenomenological interviews (20 informants: lecturers, madrasah leadership alumni, stakeholders), non-participant observation, and tracer study document analysis using NVivo thematic analysis. The University Sultan Aji Muhammad Idris Samarinda (UINSI) case study reveals the hegemony of normative fiqh content that marginalizes Islamic emotional intelligence and contextual Kutai. The prototype allocates 42% of SKS to Kutai soft skills through a systematic CPL matrix converging laman (wise research via ethnography-Delphi), bawin (collaborative leadership via 360° feedback), huma (maslahah planning via PjBL), oleh-oleh (inclusive management via workshops), and ngepa (resilient curriculum via crisis simulations), proven effective in enhancing Leadership Practices Inventory scores with confirmed behavioral transfer to madrasah management practices. The study yields a sui generis hybrid glocalization model for Islamic education that accelerates ontological decolonization of MMPI curricula via Kutai ethnopedagogy, establishing an empirical blueprint for Kemenag's Merdeka Curriculum. Mandatory prototype implementation across Kalimantan PTKIN via Ditjen Diktis policy brief, modular national cross-adat replication via transferability matrix framework, and longitudinal design-based research for sustainable madrasah leadership retention impact validation are recommended.